Analyzing the shear‐induced sensitization of mechanosensitive ion channel Piezo‐1 in human aortic endothelial cells. Issue 4 (22nd September 2020) - Lai, Austin; Chen, Yung C.; Cox, Charles D.; Jaworowski, Anthony; Peter, Karlheinz; Baratchi, Sara
Abstract: Mechanosensitive ion channels mediate endothelial responses to blood flow and orchestrate their physiological function in response to hemodynamic forces. In this study, we utilized microfluidic technologies to study the shear‐induced sensitization of endothelial Piezo‐1 to its selective agonist, Yoda‐1. We demonstrated that shear stress‐induced sensitization is brief and can be impaired when exposing aortic endothelial cells to low and proatherogenic levels of shear stress. Our results suggest that shear stress‐induced sensitization of Piezo‐1 to Yoda‐1 is independent of cell–cell adhesion and is mediated by the PI3K‐AKT signaling pathway. We also found that shear stress increases the membrane density of Piezo‐1 channels in endothelial cells. To further confirm our findings, we performed experiments using a carotid artery ligation mouse model and demonstrated that transient changes in blood‐flow pattern, resulting from a high‐degree ligation of the mouse carotid artery alters the distribution of Piezo‐1 channels across the endothelial layer. These results suggest that shear stress influences the function of Piezo‐1 channels via changes in membrane density, providing a new model of shear‐stress sensitivity for Piezo‐1 ion channel. Abstract : In this study, we utilized microfluidic technologies to study the shear‐induced sensitization of endothelial Piezo‐1 to its selective agonist, Yoda‐1. Our results suggest that shear stress influences the function of Piezo‐1 channels via changes in membrane density, providing a new model of shear‐stress sensitivity for Piezo‐1 ion channel.